A retrospective analysis of two-month sputum smear non-conversion in new sputum smear positive tuberculosis patients in the Free State Province, South Africa - Nanteza Gladys Kigozi; Perpetual Chikobvu; James Christoffel Heunis; Sonja van der Merwe (AOSIS, 2014)
Little is known about the drivers of twomonth sputum smear non-conversion in the South African context. Our study sought to determine these factors in new sputum smear positive tuberculosis (TB) patients in South Africa's Free State Province. A retrospective record review was conducted for all TB patients on treatment between 2003 and 2009. Twomonth sputum smear non-conversion was defined by a positive sputum smear result. Data was subjected to univariate, bivariate and regression analyses. Generalized linear regression models were used to estimate the risk for two-month sputum smear non-conversion. Age, pre-treatment sputum smear grading, HIV status and TB disease classification influenced two-month sputum smear non-conversion. Significant associations were thus established between health systems, microbiological, clinical and demographic factors, and two-month sputum smear non-conversion. This study provides program managers with evidence to support the development of more tailored TB care.